Obesity and education in three countries of the Central and Eastern Europe: the HAPIEE study - Pikhart, Hynek; Bobak, Martin; Malyutina, Sofia; Pajak, Andrzej; Kubínová, Růzena; Marmot, Michael (Central European journal of public health, 2007)
The international pattern of obesity is only partly understood. While in developed countries the association between education and obesity is inverse, in the developing world social distribution of obesity is less predictable. We examined obesity patterns in three countries of Central and Eastern Europe (CEE): Russia, Poland and the Czech Republic, middle-income post-communist countries undergoing social and economic transition. The prevalence of obesity was inversely associated with education of individuals in our three samples of Central and Eastern European populations. In agreement with previous findings, the inverse socioeconomic gradient was more pronounced in the Czech Republic and Poland, countries with higher Gross National Product (GNP) than Russia. In addition, obesity was more common in Russian women than in Czech or Polish women while Russian men were less obese than Czech or Polish men. These findings are consistent with the hypothesis that the social gradient in obesity differs between populations--it is more likely to find a reverse association between socioeconomic position and prevalence of obesity in the more westernized countries with higher population income.
Keywords: společenská třída; Russia; Cross-Sectional Studies; Male; Social Class; Obesity; Poland; Česká republika; obezita; prevalence; Aged; mužské pohlaví; senioři; stupeň vzdělání; Czech Republic; lidé; ženské pohlaví; Educational Status; Humans; Body Mass Index; sociální podmínky; Prevalence; průřezové studie; Rusko; Social Conditions; index tělesné hmotnosti; Female; Polsko; lidé středního věku; Middle Aged